An Overview of Commonly Used Steel Beam-Column Connection in Indonesia for Low-Rise Building - Yuana, Prima Sukma; Moestopo, Muslinang; Kusumastuti, Dyah; Pratiwi, Naomi (Politeknik Negeri Ujung Pandang, 2023)
The Indonesian seismic provision for steel structures was initiated in 2002. The use of steel has also been increasing as a choice of structural material since then. However, there are still many weaknesses in the seismic design of steel structures that have been carried out so far. A lot of beam-column connections in steel buildings in Indonesia use a haunch in a moment-resisting connection system. Haunched systems are not described in AISC 358 as permitted connections for earthquake-resistant buildings. Recently, Europe publishes European Prequalified Steel Joints (EqualJoints). There are four types of connections discussed, and one of them is the haunched type connections. The haunched connection meets the seismic requirements to be suitable for use as an earthquake-resistant connection in Europe. This can be used as a reference if we are going to design a haunched connection in Indonesia. However, special attention should be paid to the details. The bolt configuration, the thickness of the end plates, and the shape of the haunch are not like those commonly used in Indonesia, there must be improvements to be adjusted in EqualJoints. So that the performance of the connection against earthquakes becomes more guaranteed.